2010
DOI: 10.1111/j.1346-8138.2009.00743.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of human leukocyte antigen class II alleles with pemphigus vulgaris in a Turkish population

Abstract: Pemphigus vulgaris (PV) is a severe autoimmune blistering skin disorder that is strongly associated with major histocompatibility complex class II alleles. Human leukocyte antigen (HLA) subtypes vary with racial ⁄ ethnic backgrounds. The purpose of this study was to determine the association of HLA class II alleles and haplotypes with PV in Turkish patients. Twenty-five patients with PV and 113 healthy transplant donors were genotyped for HLA class II alleles. HLA DNA typing was performed by the polymerase cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 14 publications
3
26
0
Order By: Relevance
“…, 15 and the use of a small sample of patients in whom only HLA class II alleles were investigated in Tunca et al. 16 The aim of the present study was to evaluate the associations of HLA class I and II alleles and haplotypes determined by a polymerase chain reaction (PCR) with SSPs method in pemphigus patients in the Eastern Mediterranean region of Turkey.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…, 15 and the use of a small sample of patients in whom only HLA class II alleles were investigated in Tunca et al. 16 The aim of the present study was to evaluate the associations of HLA class I and II alleles and haplotypes determined by a polymerase chain reaction (PCR) with SSPs method in pemphigus patients in the Eastern Mediterranean region of Turkey.…”
Section: Introductionmentioning
confidence: 99%
“…HLA DRB1*04 allele has been found to be significantly increased in Ashkenazi Jewish patients, whereas the gene frequency of HLA DRB1*14 allele was reported to be significantly higher in pemphigus patients than in control subjects in European and American Caucasian groups, and Japanese and Mexican populations 7–11 . Although several studies on the genetic background of pemphigus have been published, only a few have reported the distribution of HLAs in Turkish populations with pemphigus 14–16 . These studies also have some limitations; HLA profiles were determined in small samples of patients, using insufficiently reliable methodology for HLA assessment or, occasionally, different techniques in the same study.…”
Section: Introductionmentioning
confidence: 99%
“…We tested 30 biopsies from patients affected by EPF in El Bagre, Colombia, South America (El Bagre-EPF) and 15 normal controls from the endemic area [3][4][5]. We also utilized 15 control skin biopsies from plastic surgery reduction patients in the USA, taken from the chest and/or abdomen.…”
Section: Subjects Of Studymentioning
confidence: 99%
“…Different HLA-DP variants can be protective, or alternatively, risk factors for infectious diseases, immune dysfunction, and autoimmunity [1][2][3]. Few studies have investigated the presence of HLA Class II in lesional skin from patients affected by ABDs [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…In our study only DRB1*14 showed to be associated beyond the threshold of multiple comparisons. Th e fact that DRB1*14 had been previously associated with several human diseases characterized either by chronic pulmonary infl ammation (sarcoidosis (35)), autoimmunity (ulcerative colitis and Pemphigus vulgaris (36)(37)) or the capacity to resolve infections (38), all of them pathogenic mechanisms postulated in COPD (5,8,(39)(40), provides biological plausibility to the possibility that DRB1*14 is a novel genetic risk factor for COPD severity.…”
Section: Interpretation Of Fi Ndingsmentioning
confidence: 94%